Development of Media Literacy Group "Creating Da’wah TV Content’’ at YPC Cintawana Vocation School. Tasikmalaya - Zakiah, Kiki; ., Askurifai; Wiksana, Wiki Angga; Suprjiadi, Yadi (KnE Social Sciences, 2023)
The PKM Development of Media Literacy Groups for Students at YPC Cintawana Vocational School, Singaparna District, Tasikmalaya Regency, West Java Province, aims to empower student groups to enhance their online media communication skills and engage in innovative da’wah activities within their school environment and for disseminating information to the public. The ongoing development of media literacy in the YPC Vocational School student group has included specialized training this year for producing da’wah TV content. The training covered various topics, including Basic Broadcasting Production, Broadcast Program Production Management, Live Streaming Podcast Youtube, and Islamic broadcasting ethics. The results of the Development of Media Literacy Groups - Creating Da’wah Content have shown positive outcomes. There has been a 15% increase in knowledge related to creating Da’wah TV content among the students. The guidance provided during the training has been effective, as the students meticulously followed the instructions given by their mentors during the 8-day training period. As a result, each group produced unique da’wah TV content with different themes and styles, based on their individual agreements with their mentors. Subsequently, their products were presented before the vice principal, teachers, and other participants in a competition. The students expressed satisfaction with their efforts in creating da’wah TV content and demonstrated fundamental skills in the process. Keywords: community service, media literacy, da’wah tv content, broadcasting